Zimbabwe: The Ethnicisation of Zanu and the Downfall of Ndabaningi Sithole (1963–2000) - Owen Mangiza; Ishmael Mazambani (Babeș-Bolyai University, 2023)
This article is an exposition of the transformation of ZANU from being, primarily, a nationalist movement into an ethnic oriented party. Since its formation in 1963, ZANU was gripped by ethnicity, resulting in factions and contestations developing among party members. These contestations developed into open conflicts along tribal lines. The paper argues that ethnicity was so acute among ZANU party members to an extent that divisions were clearly drawn along the Shona sub-ethnic groups of Manyika (easterners), Karanga (southerners), and Zezuru (northerners). The competition for leadership positions and the fighting among members of these ethnic groups resulted in the death of some members of the party and the expulsion of others from the party. It is argued in the article that the persecution of Ndabaningi Sithole and his fallout as the ZANU president was a result of the ethnicisation of ZANU and the liberation struggle. The removal of Sithole as the party president and his replacement by Robert Mugabe exhibits these contestations among the Zezuru, Karanga and Manyika ethnic groups. We argue that the deposition of Sithole from ZANU in 1975 and his castigation as a “sell-out” and “tribalist” was a ploy by Robert Mugabe and other ZANU leaders to get rid of him and to replace him along ethnic grounds. The ethnic card was deployed to serve selfish political interests. It is these ethnic contestations and fighting which also brewed conflict and enmity between Mugabe in particular and Ndabaningi Sithole, among other factors. This hatred was clearly displayed later in the struggle for supremacy between Sithole’s new party, ZANU-Ndonga and Robert Mugabe’s ZANU-PF. It is stressed in the article that this enmity also culminated in the denial of a hero status to Sithole when he died in 2000. We also argue that the deposition of Sithole from ZANU is one of the reasons why the Ndau people of Chipinge always voted for him and not Robert Mugabe in elections.